Latin America : today's economic and social revolution - Powelson, John P. (New York ; London : McGraw-Hill, 1964)
This volume examines include agrarian reform, "monopoly" (the market mechanism, foreign investment), commodity agreements (with four case studies), inflation, economic integration, foreign aid, and national economic planning with reference to Latin America.
Includes bibliographical footnotes and index.
lje 03/10/2018
Loans
Keywords: Economic growth; Latin America